Aryloxoalcanoic compounds induce resistance to antibiotic therapy in urinary tract infection caused by Escherichia coli - Balague, Claudia Elisabeht (2006)
Clofibric acid (CL) is a compound used to control hypertriglyceridemia, and ethacrynic acid (ET) is administered to enhance diuresis. These compounds are structurally analogous to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D), as they have a chlorinated phenoxy moiety. As these agents are mainly excreted by the renal route, they could potentially coexist with Escherichia coli in the urinary tract of infected patients. Induction of the in vitro resistance of E. coli to hydrophilic antibiotics was determined by increasing the values of the minimum inhibitory concentration (2-40-fold). These results correlated with drastically inhibited expression of the hydrophilic bacterial channel OmpF. In vivo assays were performed in ascending urinary tract infection in female BALB/c mice. Treatment with the hydrophilic antibiotic cephalexin 25 mg kg -1 day-1 by the oral route diminished renal infection. The CFU mean values in the kidneys were between 75% and 89% lower than those in animals without treatment. Simultaneous exposure to CL (at a therapeutic dose, 28.6 mg kg-1 day-1) did not change the effect of the treatment. In contrast, ET at 2.9 mg kg-1 day-1 or 2,4-D at 70 mg kg-1 day-1 inhibited the antibiotic therapeutic effect. Moreover, 2,4-D dramatically increased bacterial infection after 9 days of exposure.